Metabolic disorders and morpho-densitometric parameters of the hypothalamic neurons, pathogenetic relationships with experimental stress - Kryvsun, Kostiantyn (Тернопільський державний медичний університет імені І. Я. Горбачевського, 2019)
The hypothalamus, including its supraoptic (SON) and paraventricular nuclei (PVN), is the key conductor in triggering the body's stress response. But there are almost no defined data about changes in the parameters of its neurons and development of metabolic disorders in social stress. The aim of the work was to establish the correlation of changes in the morpho-densitometric parameters of magnocellular neurons of PVN and SON of male Wistar rats in social stress with the formed metabolic disorders.